DIfferential Subsampling With Cartesian Ordering With Respiratory Triggering Versus Conventional Liver Acquisition With Volume Acquisition: A Multiple Reader Preference Study - Allen, Brian C; Ehieli, Wendy L; Wildman-Tobriner, Benjamin; Chaudhry, Mohammad; Bozdogan, Erol; Janas, Gemini; Ronald, James; Bashir, Mustafa R (Journal of computer assisted tomography, 2019)
The aim of this study was to compare respiratory-triggered DIfferential Subsampling with Cartesian Ordering (rtDISCO) and breath-held Liver Acquisition with Volume Acquisition (LAVA) image quality. In this institutional review board-approved, Health Insurance Portability and Accountability Act-compliant prospective study, 25 subjects underwent T1 imaging with rtDISCO and LAVA before and after intravenous contrast. Three readers scored individual series and side-by-side comparisons for motion and noise. Eight clinical tasks were qualitatively assessed. As individual series, readers rated rtDISCO images as more degraded by motion on both precontrast (mean rtDISCO score, 2.7; LAVA, 1.6; P < 0.001) and postcontrast images (rtDISCO, 2.4; LAVA, 1.8; P < 0.001). Readers preferred LAVA images based on motion on both precontrast (mean preference, -1.2; P < 0.001) and postcontrast images (mean preference, -0.7; P < 0.001) on side-by-side assessment. There was no preference between sequences for 6 of 8 clinical tasks on postcontrast images. Readers preferred LAVA with respect to motion but not noise; there was no preference in most of the tested clinical tasks.